Did school food and nutrient-based standards in England impact on 11-12Y olds nutrient intake at lunchtime and in total diet? Repeat cross-sectional study. - Suzanne Spence; Jennifer Delve; Elaine Stamp; John N S Matthews; Martin White; Ashley J Adamson (PLoS ONE)
Introduction In September 2009, middle and secondary schools in England were required to comply with food and nutrient-based standards for school food. We examined the impact of this policy change on children's lunchtime and total dietary intake. Methods We undertook repeat cross-sectional surveys in six Northumberland middle schools in 1999-2000 and 2009-10. Dietary data were collected from 11-12 y olds (n = 298 in 1999-2000; n = 215 in 2009-10). Children completed two consecutive 3-day food diaries, each followed by an interview. Linear mixed effect models examined the effect of year, lunch type and level of socio-economic deprivation on children's mean total dietary intake. Results We found both before and after the introduction of the food and nutrient-based standards children consuming a school lunch, had a lower per cent energy from saturated fat (-0.5%; p = 0.02), and a lower intake of sodium (-143 mg; p = 0.02), and calcium (-81 mg; p = 0.001) in their total diet, compared with children consuming a home-packed lunch. We found no evidence that lunch type was associated with mean energy, or absolute amounts of NSP, vitamin C and iron intake. There was marginal evidence of an association between lunch type and per cent energy NMES (p = 0.06). In 1999-2000, children consuming a school lunch had a higher per cent energy from fat in their total diet compared with children consuming a home-packed lunch (2.8%), whereas by 2009-10, they had slightly less (-0.2%) (year by lunch type interaction p<0.001; change in mean differences -3%). Conclusions We found limited evidence of an impact of the school food and nutrient-based standards on total diet among 11-12 year olds. Such policies may need to be supported by additional measures, including guidance on individual food choice, and the development of wider supportive environments in school and beyond the school gates.